An Overview of Polymeric Hydrogel Applications for Sustainable Agriculture - Vedovello, Priscila [UNESP]; Sanches, Lívia Valentim [UNESP]; da Silva Teodoro, Gabriel [UNESP]; Majaron, Vinícius Ferraz; Bortoletto-Santos, Ricardo; Ribeiro, Caue; Putti, Fernando Ferrari [UNESP] (MDPI, 2024)
Agriculture, a vital element of human survival, confronts challenges of meeting rising demand due to population growth and product availability in developing nations. Reliance on pesticides and fertilizers strains natural resources, leading to soil degradation and water scarcity. Addressing these issues necessitates enhancing water efficiency in agriculture. Polymeric hydrogels, with their unique water retention and nutrient-release capabilities, offer promising solutions. These superabsorbent materials form three-dimensional networks retaining substantial amounts of water. Their physicochemical properties suit various applications, including agriculture. Production involves methods like bulk, solution, and suspension polymerization, with cross-linking, essential for hydrogels, achieved through physical or chemical means, each with different advantages. Grafting techniques incorporate functional groups into matrices, while radiation synthesis offers purity and reduced toxicity. Hydrogels provide versatile solutions to tackle water scarcity and soil degradation in agriculture. Recent research explores hydrogel formulations for optimal agricultural performance, enhancing soil water retention and plant growth. This review aims to offer a comprehensive overview of hydrogel technologies as adaptable solutions addressing water scarcity and soil degradation challenges in agriculture, with ongoing research refining hydrogel formulations for optimal agricultural use.
Keywords: agricultural technology; cross-linking; grafting techniques; hydrogels; nutrient release; soil water retention